Effect of Y and Gd content on the microstructure and mechanical properties of Mg–Y–RE alloys - Kang Luo; Liang Zhang; Guohua Wu; Wencai Liu; Wenjiang Ding (Journal of Magnesium and Alloys, 2019)
In the application of WE43, it is found that Y2O3 inclusion formed in the process of casting seriously reduced the mechanical properties of the products. The reduction of the mechanical properties is even more distinct when it comes to the application in the thin walled complex-precision castings. In order to decrease the Y2O3 inclusions, Gd element was used to replace part of the Y element in Mg-Y-RE series alloys. The effect of Y content (Mg-xY-1Gd-2Nd-0.5Zn-0.5Zr) and Y/Gd ratio (Mg-xY-(5-x)Gd-2Nd-0.5Zn-0.5Zr) on the microstructure and mechanical properties of Mg–Y–RE alloys were investigated in this paper. With decreasing Y content, the grain size of the alloys increased, both ultimate tensile strength (UTS) and yield strength (YS) of alloys decreased monotonically. Replacing part of Y content with Gd and keeping the total rare earth content unchanged, the low Y content Mg-2Y-3Gd-2Nd-0.5Zn-0.5Zr alloy showed the same mechanical properties as the high Y content Mg-4Y-1Gd-2Nd-0.5Zn-0.5Zr alloy at both room and elevated temperatures. After solution treatment at 525 °C for 8 h and aging treatment at 225 °C for 10 h, the UTS, YS and elongation (ε) of Mg-2Y-3Gd-2Nd-0.5Zn-0.5Zr alloy reached 281.7 MPa, 198 MPa and 11.1% at room temperature, and 216.7 MPa, 171.6 MPa and 16.1% at 250 °C. The new low Y content Mg-2Y-2Nd-3Gd-0.5Zn-0.5Zr alloy is expected to replace the high Y content WE43 alloys, which can be used in the complex thin-walled parts of aviation products. Keywords: Mg–Y–RE alloy, Microstructure, Mechanical property, Y/Gd ratio, Heat treatment